Meta-analysis of the studies of seventy years of development planning, in order to be used in compiling the seventh development plan - Morteza Mehralitabar Firoozjaei; Gholamreza Garainejad (پژوهش‌های برنامه و توسعه)
The main issue of the present study is one of the most important steps in the development of the development plan, which is called the "Development Plan System". This Plan System refers to all organized processes and operations that include the steps of preparing, compiling, approving and communicating the program. Therefore, considering the importance of the subject, this study aims to define and explain the elements of the seventh development plan. Through a meta-analytical study of the Seventy Years of Development Planning studies, it tries to analyze the codes of previous development programs from a structural-content perspective and to discuss the concepts and propositions contained in them. The target population of this research is a collection of studies of seventy years of development planning and the extraction of propositions has been pursued to the point of theoretical saturation. After extracting the propositions, they have been analyzed by qualitative content analysis with an inductive approach. In fact, research data are divided into meaning units and then summarized by compression. Finally, the subclasses are extracted by inductive method and the main themes are abstracted from them. The analysis of the findings shows that the extracted themes can be classified into social-cultural, economic, environmental-planning, institutional-structural and systematic categories, which are important to consider in developing the seventh plan.  Also, by overlapping and using the common chapter of the extracted themes, eight orientations were obtained, which show the general direction of the seventh development plan. Finally, below each of the extracted orientations, their policies and requirements are presented in accordance with the research findings.